Evaluasi Perencanaan Pembiayaan Pembangunan Infratruktur Pendidikan di PKN STAN Melalui Skema Kerjasama Pemerintah Dengan Badan Usaha - Novitasari Putri Ramadhani; Muhammad Heru Akhmadi (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2021)
This study aims to determine the mechanisms and arrangements for PPP planning according to applicable regulations, to know the urgency of PPP implementation at PKN STAN, and to find out the form of government support for PPP implementation at PKN STAN. The researceh use qualitative research with a descriptive approach. The data were obtained through interviews and literature study by analyzing regulations and journals related to PPP planning. Data analysis was carried out using ATLAS.ti 8. The results revealed that there were seven activities in PPP planning which included the preparation of the PPP fund budget plan, identification and determination of the PPP, budgeting of funds at the PPP planning stage, public consultation, decision making whether or not to proceed. further PPP plans, preparation of the List of PPP Plans, and categorization of PPPs. The selection of the PPP scheme at PKN STAN was carried out due to funding constraints, the lack of human resources at PKN STAN who have a background in construction, and concerns about the lack of efficiency in the implementation of PKN STAN development if funded through pure rupiah. In addition, the implementation of PPP in PKN STAN will save 15 years of PKN STAN infrastructure procurement. The type of government support proposed by PKN STAN is the Project Preparation Facility (PDF) to assist the PJPK in increasing the effectiveness of the implementation of PPP preparation and transactions in order to meet the specified quality and time.